Handyman Wanted - 20 Sexy Erotic Short Stories - Bocker, Britta (Saga Egmont, 2023)
Handyman Wanted - 20 Sexy Erotic Short Stories\' is a collection from LUST that explores many different sexual fantasies. From polyamory and sex clubs to voyeurism and visits from the handyman, your sexy fantasies will be fulfilled with this collection.